MTT FORMAZAN REPLACED WST-8 AS A BETTER SIMPLE SCREENING METHOD FOR DETECTION OF GLUCOSE-6-PHOSPHATE DEHYDROGENASE DEFICIENCY - Tantular, Indah (Institute of Topical Disease Universitas Airlangga, 2019)
We have previously developed the WST-8 method as a simple and rapid screening test for detection of glucose-6-phosphate dehydrogenase (G6PD) deficiency accomplished by the naked eye. However, it was little difficult to distinguish between faint orange colors developed by heterozygous females and pink colors of normal hemolyzed blood, since both have similar tones. To solve this problem, we established a new and simple screening method that utilizes another formazan substrate, MTT (3-(4,5-dimethyl-2- thiazolyl)-2,5-diphenyl-2H tetrazolium bromide) in combination with a hydrogen carrier, 1-methoxy phenazine methosulfate. MTT formazan exhibits a purple color, thus allowing for the ability to easily distinguish the pink colors of hemolyzed blood. However, MTT has been reported to react with hemoglobin non-specifically and to interfere with the interpretation of the color reaction. In our examinations by mixing MTT with hemolyzed blood, we found that the non-specific reaction was very slow, and that the addition of a small amount of blood (5 10 Î¼l) into a reaction mixture (800 Î¼l) did not interfere with the reaction of G6PD activity. In this new MTT method, a strong purple color was generated in normal blood samples at 20 30 min after incubation, which could be distinguished by the naked eye from G6PD-deficient blood samples with less than 50% residual activity. In addition, quantitative measurement using a spectrophotometer was also possible despite the fact that MTT formazan is water-insoluble.